Evidence of a role for galectin-1 in acute inflammation - Rabinovich, Gabriel Adrián (2000)
Galectin-1 (Gal-1), a member of a family of beta-galactoside-binding proteins, has been suggested to play key roles in immunological and inflammatory processes. The present study deals with the concept of an in vivo role for Gal-1 in acute inflammation by using the rat hind paw edema test. Local administration of Gal-1 (0.5, 2, 4 and 8 microg/ml) inhibited acute inflammation induced by bee venom phospholipase A(2) (PLA(2)) when it was injected 30 min before the enzyme or co-injected together with PLA(2). The anti-inflammatory effect was prevented by a specific antibody, but independent of its carbohydrate-binding properties. In contrast, Gal-1 failed to inhibit histamine-induced edema. Histopathological studies showed a clear reduction of the inflammatory process when Gal-1 was injected before PLA(2), evidenced by a diminished number of infiltrated polymorphonuclear neutrophils and scarce degranulated mast cells. The anti-inflammatory effect was also assessed in vitro, showing that Gal-1 treatment reduced prostaglandin E(2) secretion and arachidonic acid release from stimulated peritoneal macrophages. Results presented here provide the first evidence for a role of Gal-1 in acute inflammation and suggest that the anti-inflammatory effect involves the inhibition of both soluble and cellular mediators of the inflammatory response.